2009
DOI: 10.1203/pdr.0b013e3181a9e818
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Allele of IGF2 Gene Haplotype CTG Is Associated With Fetal and Placental Growth in Japanese

Abstract: IGF-II associates with feto-placental growth in rodent and human. We determined three tag-single nucleotide polymorphisms (SNPs) to investigate haplotype frequency of IGF2 relative to size at birth in 134 healthy Japanese infants. In addition, a total of 276 healthy infants were investigated to determine whether common genetic variation of IGF2 might contribute to feto-placental growth using haplotype analysis. Further, quantitative methylation analysis of the IGF2/H19 was performed using the MassARRAY Compact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Additional SNPs that were associated with SGA at a p -value of < 0.05 are presented in Table 5. Although we have not emphasized these findings in the present report, in some instances they represent associations in pathways previously reported, (e.g., IGF1R and IGF1 in the present report and IGF2 in Nagaya et al[108]) that may lend support to previous findings or may be additional SNPs in genes reported with a p -value < 0.01. Such findings strengthen the likelihood of an association because they are based on multiple SNPs for the same gene.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Additional SNPs that were associated with SGA at a p -value of < 0.05 are presented in Table 5. Although we have not emphasized these findings in the present report, in some instances they represent associations in pathways previously reported, (e.g., IGF1R and IGF1 in the present report and IGF2 in Nagaya et al[108]) that may lend support to previous findings or may be additional SNPs in genes reported with a p -value < 0.01. Such findings strengthen the likelihood of an association because they are based on multiple SNPs for the same gene.…”
Section: Resultssupporting
confidence: 58%
“…Of note, in contrast to data on maternal genes, fetal genetic predisposition to SGA has been even less studied. [97,108]…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that imprinted regions can harbor genetic variants that influence phenotype in a parentalorigin-specific manner, with opposite effects associated with maternally-and paternally-inherited alleles. 35 Of note, polymorphisms at human 11p15.5 have been shown to have a parent-oforigin specific association with placental and fetal growth 36,37 and type-2 diabetes. 38 The parent-of-origin specific effect on cerebellum weight observed in our analyses resembles the "bipolar dominance" pattern of imprinting previously reported for postnatal growth at imprinted regions in mice 39 and with birth weight in humans, 36 whereby heterozygous individuals stratified by paternally-and maternally-inherited alleles have opposite phenotypes, with homozygous individuals showing intermediate levels.…”
Section: Discussionmentioning
confidence: 99%
“…BWS is characterized by pre- and postnatal overgrowth and is commonly associated with altered methylation of DMRs near H19 and KCNQ1 (500 Kb from IGF2) and their loss of imprinting. Among Japanese, inferred paternal inheritance of IGF2 haplotype CTG at rs1003484, rs3741211 and rs3741206 was associated with a higher frequency of SGA births (25). We observed a significant association between birth weight and newborn genotypes at rs3741205 for both an additive and recessive (TT vs. GT and GG) model.…”
Section: Discussionmentioning
confidence: 99%